2018
DOI: 10.3748/wjg.v24.i11.1216
|View full text |Cite
|
Sign up to set email alerts
|

Differing profiles of people diagnosed with acute and chronic hepatitis B virus infection in British Columbia, Canada

Abstract: AIMTo describe the characteristics of people diagnosed with acute and chronic hepatitis B virus (HBV) infection in British Columbia (BC).METHODSWe used data from the BC Hepatitis Testers Cohort (BC-HTC), which includes all individuals tested for hepatitis C virus (HCV) or human immunodeficiency virus (HIV) or those diagnosed with HBV or active tuberculosis in BC since 1990. These data were integrated with prescription drug, medical visit, hospitalization and mortality data. HBV cases were classified as acute o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
5
18
0
Order By: Relevance
“…The odds of hepatitis C viral infection were 1.5 folds higher among tuberculosis patients with problematic alcohol use. This finding was in line with previous work [ 39 , 40 ]. This is because people with problematic alcohol use can commit unprotected sexual intercourse that exposes them to acquire the virus more easily [ 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…The odds of hepatitis C viral infection were 1.5 folds higher among tuberculosis patients with problematic alcohol use. This finding was in line with previous work [ 39 , 40 ]. This is because people with problematic alcohol use can commit unprotected sexual intercourse that exposes them to acquire the virus more easily [ 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…In both studies high values were reported for chronic infection however, the difference between our findings and those from the Colombian study may be because our study was a cross-sectional and sample size was 254 participants. Our findings are reflective of what is happening elsewhere in that many individuals have chronic hepatitis B [15]. The greatest (95%) transmission of HBV is during perinatal period, 30% in children below the age of 5 [2].…”
Section: Type Of Hepatitis B Infection (Acute or Chronic)supporting
confidence: 73%
“…In our study 33.3% of those actively infected with HBV were positive for the HepB core IgM, 66.7% had negative HBcAb IgM but positive HBcAb IgG an indication of chronic hepatitis B infection [14]. In a cohort study with over 1.7 million individuals done in British Colombia from 1990-2015 describing the characteristics of people diagnosed with acute and chronic hepatitis B virus (HBV) infection, 4.3% of the individual had acute Hepatitis B infection and 95.7% of the individuals had chronic infection [15]. In both studies high values were reported for chronic infection however, the difference between our findings and those from the Colombian study may be because our study was a cross-sectional and sample size was 254 participants.…”
Section: Type Of Hepatitis B Infection (Acute or Chronic)mentioning
confidence: 99%
“…Assessment of injection drug use (IDU) and problematic alcohol use was based on diagnostic codes ( Supplementary Table 1 ) for medical visits and hospitalizations in respective databases. Ethnicity was classified on the basis of validated name recognition software Onomap, as reported previously [ 20 ]. The algorithm has high sensitivity and specificity for South Asian and East Asian peoples, with the exception of Filipinos.…”
Section: Methodsmentioning
confidence: 99%